Effect of pregnant mare serum gonadotrophin injection on litter size in young Etawah-cross does - N.M Artiningsihi; B Purwantara; R.K Achjadi; I-K Sutama (Jurnal Ilmu Ternak dan Veteriner, 1996)
The incidence of twins and/or multiple births in 20 heads of young Etawah-cross does was studied following oestrous synchronization using intravaginal sponges containing 60 mg medroxyprogesterorle acetate (Repromap) for 15 days . Twenty four hours priorto sponges withdrawal, the does were injected with pregnant mare serum gonadotrophin (PMSG) at dose rates of 0 (Group A), 10 (Group B), 15 (Group C) and 20 iu/kg (Group D) body weight. Amature buck fitted with an apron was used to detect the onset of oestrus at every four hours. The oestrous doe was naturally mated twice, 12 hours after onset of oestrus and 10 hours later. About 3-5 days after oestrus, all does were subjected to mid-ventral laparoscopy to detect ovulation rate . Two months after mating all does were subjected to pregnancy test using diagnostic ultrasonography. Results showed that all does exhibited clear sign of oestrus. The onset of oestrus occurred 15-43 hours after sponges withdrawal or 39-59 hours after PMSG injection. Does injected with PMSG (Groups B, C and D) showed oestrus 16-21 hours earlier (P<0.05), and it was 1 .6-4.8 hours longer (P>0 .05) than that of control (Group A) . However, there was no significant differences among the PMSG-treated groups . Ovulation rates increased from 1.0 in Group Ato 1.8 in Group B and 2.6 in bah Groups Cand D. Average litter size in Groups A, B, C and D were 1.0, 1.8, 2.4 and 1.0, respectively. It was concluded that injection of 15 iu PMSG/kg body weight gave the best result for increasing litter size in young Etawah-cross does .   Key words: Etawah-cross, PMSG, synchronization, reproduction